2015
DOI: 10.1016/j.ogrm.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum pyrexia

Abstract: Postpartum pyrexia occurs in 5e7% of births. There are many possible causes, with infection related to childbirth being the most common. In women presenting with non-specific symptoms, the diagnosis of puerperal sepsis should be considered until proven otherwise, as puerperal sepsis can result in severe maternal morbidity and occasional mortality. A comprehensive history and physical examination supported by appropriate investigations can help confirm the diagnosis. Use of an early warning chart for observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 4 publications
2
13
6
Order By: Relevance
“…However, our findings contrary to other studies [3,12], found no association between PP and prolonged rupture of membranes (PROM). This is probably due to routine use of broad spectrum antibiotics in patients with PROM at the DGH, as prophylaxis for chorioamnionitis and subsequent neonatal sepsis.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, our findings contrary to other studies [3,12], found no association between PP and prolonged rupture of membranes (PROM). This is probably due to routine use of broad spectrum antibiotics in patients with PROM at the DGH, as prophylaxis for chorioamnionitis and subsequent neonatal sepsis.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous reviews [3,10] which reported puerperal sepsis as the leading cause of postpartum pyrexia, malaria was the single most frequent cause of postpartum pyrexia observed in this study. The high incidence of postpartum malaria observed is typical to that described in a Gabonese study [20], which revealed that puerperal women were susceptible to a considerable risk of developing malaria.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations